2017
DOI: 10.1155/2017/4304973
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Related Adverse Drug Reactions at a Tertiary Care Hospital in South Korea

Abstract: Background Adverse drug reactions (ADRs) are any unwanted/uncomfortable effects from medication resulting in physical, mental, and functional injuries. Antibiotics account for up to 40.9% of ADRs and are associated with several serious outcomes. However, few reports on ADRs have evaluated only antimicrobial agents. In this study, we investigated antibiotic-related ADRs at a tertiary care hospital in South Korea. Methods This is a retrospective cohort study that evaluated ADRs to antibiotics that were reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 26 publications
7
29
1
1
Order By: Relevance
“…major proportions of adverse reactions were seen with beta-lactam antibiotics (37.5%) which were similar to the observations by Akalu and Belavadi as well as by Jung et al [12,13]. Beta-lactam antibiotics are one of the widely used antibiotics for a wide variety of infections.…”
Section: James and Ranisupporting
confidence: 88%
See 1 more Smart Citation
“…major proportions of adverse reactions were seen with beta-lactam antibiotics (37.5%) which were similar to the observations by Akalu and Belavadi as well as by Jung et al [12,13]. Beta-lactam antibiotics are one of the widely used antibiotics for a wide variety of infections.…”
Section: James and Ranisupporting
confidence: 88%
“…Also, the patients admitted in these departments have comorbidities that require polypharmacy, which accounts for the high number of ADRs. Following the previous studies by Mahatme and Narasimharao, Gupta et al, and Jung et al, the present study showed the predominance of cutaneous manifestations on presentation of ADRs (75%) [13][14][15] followed by central nervous system manifestations such as dizziness. However, several other studies have observed gastrointestinal symptoms such as vomiting and diarrhea as the most common manifestation of ADR [16][17][18].…”
Section: James and Ranisupporting
confidence: 85%
“…With the exception of anticancer drugs, the occurrence of cutaneous ADRs with other group of drugs were similar to previous studies done by Manjhi and Sharma. 25,27 When cutaneous ADRs due to antimicrobials were analysed further, it was observed that fluoroquinolones, cephalosporins, penicillins and glycopeptide antibiotics were responsible for majority of cutaneous ADRs reported and this findings were consistent with the study done by Jung et al 28 Most cases of maculopapular rash in the present study was caused by antimicrobial drugs (25.71%), followed by NSAIDs (14.28%), anticancer drugs (11.42%) and antiepileptics (10%). Our study differ from others, where antiepileptic drugs were responsible for more than 50% cases of maculopapular eruptions.…”
Section: Discussionsupporting
confidence: 89%
“…In the Greece study more, number of antibiotics induced reactions had been reported by nurses than the faculties. 9,10 Even though the total number of ADR reports by nurses was small, this analysis indicates that instructed and interested nurses could play an important role in detecting and reporting suspected ADRs. The reporting tendency of ADRs mostly relies upon the attitude of the person who notifies and also personal and professional factors.…”
Section: Discussionmentioning
confidence: 87%